Malnutrition coding and reimbursement in the hospital setting. (29th September 2021) - Shepherd, Erin
Abstract: Professionals responsible for the nutrition care of hospitalized patients should understand the prevalence of malnutrition, how to accurately and consistently identify and communicate a diagnosis of malnutrition in the medical record, and the sophisticated payment systems used to reimburse hospitals for patient care. Insight into healthcare payment systems and the requirements for clarity, consistency, and accuracy can improve identification, coding, and billing for malnutrition. Hospitals receive reimbursement for services based on anticipated costs for diagnosis‐based groups, and documenting the presence of a comorbidity, such as malnutrition, can increase the payment for a diagnosis. It is important to accurately document not only the supporting criteria used to diagnose malnutrition, but also the interventions used to address it during a patient's stay.